IMPROVEMENT OF THE MECHANISM OF TECHNOLOGY TRANSFER WITHIN THE CONTEXT OF THE INNOVATIVE DEVELOPMENT OF THE AGROINDUSTRIAL COMPLEX OF RUSSIA - Mikhail Yakovlevich VESELOVSKY; Vladimir Gavrilovich SAVENKO; Inna Vladimirovna BITKINA; Natalia Lvovna KRASYUKOVA; Aleksandr Annayarovich STEPANOV (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The article reveals the problems of the development and improvement of the activity of entities of agricultural consulting in Russia in the period of the large-scale modernization of the agroindustrial complex. Special attention is paid to the problem of participation of the educational institutions subordinated to the Ministry of Agriculture in the consulting activity and to promoting the innovative activity of the participants in the innovative process. The current state of the institute of agricultural consulting, the main results of the activity in 2017 and the proposals for its development for the mid-term perspective are described. The priority directions and the strategy for the development of agricultural consulting are formulated in regard to the modernization of agricultural production, structural changes in its organization and the development of the system of agricultural consulting. The main directions of development of the institute of agricultural consulting, the main performed functions and the expected results are represented, as well as their impact on improving the quality of the informational and consulting support of agricultural production. The necessity of corrections of the conceptual essentials of the complex development of the institute of agricultural consulting is grounded including the ones organized with participation of educational institutions.